2017
DOI: 10.1002/joe.21811
|View full text |Cite
|
Sign up to set email alerts
|

More than makeup: How Atsoko overcame the challenges of entrepreneurship in Tanzania

Abstract: Africa is an emerging economy with many institutional obstacles that complicate efforts to do business there. These include limited access to capital, a lack of skilled labor, inferior infrastructure, and corruption. The experiences of Marie Englesson, a Swedish entrepreneur, in establishing Atsoko, a thriving cosmetics distribution and retailing firm in Tanzania, offer valuable lessons in addressing those challenges through creativity, dedication, and wise and principled deployment of capital.Securing first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 7 publications
5
15
0
Order By: Relevance
“…This is a sure method to measure the viability of an innovation. These findings are in line with Wang et al (2005) and Alon and Shneor (2017) who emphasised the need to measure business fit by means of survey. In this, an idea is developed based on an existing gap, and is then tested for quality control before execution (Alon & Shneor 2017;Darnihamedani 2016).…”
Section: Risk Awarenesssupporting
confidence: 88%
See 2 more Smart Citations
“…This is a sure method to measure the viability of an innovation. These findings are in line with Wang et al (2005) and Alon and Shneor (2017) who emphasised the need to measure business fit by means of survey. In this, an idea is developed based on an existing gap, and is then tested for quality control before execution (Alon & Shneor 2017;Darnihamedani 2016).…”
Section: Risk Awarenesssupporting
confidence: 88%
“…Participants' view of R and business sustainability corroborate those of Alon and Shneor (2017) who asserted that real entrepreneurs endure uncertainties and see how they could transform them into opportunities, whilst others give up. Lack of R would continue to impact negatively on entrepreneurs who have low potential to survive and succeed.…”
Section: Resiliencementioning
confidence: 54%
See 1 more Smart Citation
“…And while entrepreneurs deal with adversity regardless of context, some challenges reign prominent in African contexts in general (e.g. Alon and Shneor 2017;Belwal and Singh 2008) and the African crowdfunding context in particular.…”
Section: Challenges For the Development Of Crowdfunding In Africamentioning
confidence: 99%
“…Research has shown that passion helps an entrepreneur perform better-that it leads toward a higher entrepreneurial effort (Baum, Locke, & Smith, 2001) and to greater persistence (Cardon & Kirk, 2013). Starting a new business venture is demanding and requires a continual and consistent effort on the part of an entrepreneur (Alon & Shneor, 2017). Furthermore, this effort might require entrepreneurs to invest time and financial capital over several years to make their business successful (Gielnik, Spitzmuller, Schmitt, Klemann, & Frese, 2014).…”
Section: What Is Entrepreneurial Passion?mentioning
confidence: 99%